Differences in endophyte communities of introduced trees depend on the phylogenetic relatedness of the receiving forest. (September 2016) - Gundale, Michael J.; Almeida, Juan P.; Wallander, Håkan; Wardle, David A.; Kardol, Paul; Nilsson, Marie‐Charlotte; Fajardo, Alex; Pauchard, Aníbal; Peltzer, Duane A.; Ruotsalainen, Seppo; Mason, Bill; Rosenstock, Nicholas
Summary: Plant species sometimes perform extraordinarily well when introduced to new environments, through achieving higher growth rates, individual biomasses or higher densities in their receiving communities compared to their native range communities. One hypothesis proposed to explain enhanced performance in species' new environments is that their soil microbial communities may be different and provide greater benefit than microbial communities encountered in species' native environments. However, detailed descriptions of soil biota associated with species in both their native and introduced environments remain scarce. We established a global network of sites in regions where the tree species Pinus contorta has been introduced (Chile, New Zealand, Finland, Scotland and Sweden), as well as native range sites where the introduced populations originated (Canada and USA). We conducted pyrosequencing analysis to compare the root fungal endophyte communities associated with P. contorta in its native environments and in introduced environments with phylogenetically similar and dissimilar tree species (i.e. P. sylvestris in Europe and Nothofagus spp. in the Southern Hemisphere). Fungal communities associated with P. contorta consistently differed between its introduced and native environments. In Europe, P. contorta associated with the same community as P. sylvestris, where one particular species ( Piloderma sphaerosporum ) was particularly abundant relative to Canadian sites. In the Southern Hemisphere, P. contorta fungal communities were composed primarily of North American taxa and exhibited very little overlap with fungal communities associated with native Nothofagus spp. Synthesis . Our work shows that plants exhibit considerable plasticity in their interaction with fungi, by associating with different fungal communities across native and introduced environments. Our work also indicates that fungal communities associated with introduced plants can assemble through different mechanisms, that is by associating with existing fungal communities of phylogenetically close species, or through reassembly of co‐introduced and co‐invading fungi. The identification of different fungal communities in a plant species new environment provides an important step forward in understanding how soil biota may impact growth and invasion when a species is introduced to new environments. Abstract : Our work shows that plants exhibit considerable plasticity in their interaction with fungi, by associating with different fungal communities across native and introduced environments. Our work also indicates that fungal communities associated with introduced plants can assemble through different mechanisms, that is by associating with existing fungal communities of phylogenetically close species, or through reassembly of co‐introduced and co‐invading fungi. The identification of different fungal communities in a plant species new environment provides an important step forward in understanding how soil biota may impact growth and invasion when a species is introduced to new environments.